Unbound from Rome art and craft in a fluid landscape, ca. 650-250 BCE - Hopkins, John North (Yale University Press, 2024)
"Roman art and architecture is typically understood as being bound in some ways to a political event or as a series of aesthetic choices and experiences stemming from a center in Rome itself. Moving beyond the misleading catchall label "Roman," John North Hopkins aims to untangle the many peoples whose diverse cultures and traditions contributed to Rome’s visual culture over a four-hundred-year time span across the first millennium BCE. Hopkins carefully reconsiders some of the period’s most iconic works by way of the many practices and peoples bound up with them. Some of these include the extraordinary and complex effort to build the Temple of Jupiter; the creative actions and diverse encounters tied to luxury objects like the Ficoroni Cista; and the important meanings held by sacred temple sculpture and votive offerings through their making and subsequent practices of devotion. A key purpose of this book is to question an idea of Rome that has focused on elite production and the textual record; Hopkins instead calls attention to the lesser-known—often silenced—actors who were integral players. The result is a deep understanding of a diverse and historically rich Italic and Mediterranean world, as well as the myriad cultures, communities, and individuals who would have made and experienced art within and around the changing political boundaries of Rome"--
Keywords: Geschichte 650 v. Chr.-250 v. Chr.; Kunst; Handwerk; Römisches Reich; Art and society / Rome; Art, Roman; Architecture, Roman; Rome / Antiquities; Decoration and ornament, Roman; Art et société / Rome; Art romain; Architecture romaine; Rome / Antiquités